PENGEMBANGAN MODUL AJAR IPAS BERBASIS PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V SD - Mutoharoh; Suriswo; Dewi Apriani Fr (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the validity, effectiveness, and practicality of the Problem Based Learning (PBL)-based science learning module in improving students' critical thinking skills on the material "My Dear Earth, My Poor Earth" in grade V of elementary school. The background of the study is the low critical thinking skills of students and the lack of teaching modules that integrate the PBL model. By implementing the PBL approach, it is expected to create an active, collaborative, and student-centered learning atmosphere, as well as encourage student involvement in solving real problems related to everyday life. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, as well as experimental and control designs. The results of the questionnaire showed that the PBL-based science module developed was very feasible to use with a feasibility percentage of 86.95% (material), 88.57% (media), and 85% (module/design). The practicality of the module was also high, with student responses of 86.11% and teacher responses of 87.66%, both of which were included in the very practical category. Thus, this module is declared valid, effective, and practical to improve students' critical thinking skills.